Abundance and Characteristics of Microplastics in the Soil of a Higher Education Institution in China - Tang, Kuok Ho Daniel; Luo, Yuxin (Tropical Aquatic and Soil Pollution, 2023)
While microplastics have been detected in various spheres of the environment, there are few studies examining their abundance in higher education institutions, where their exposure to students and staff could raise concern. This study aims to quantify and characterise the microplastics in the soil of a higher education institution in China. Surface soil samples were collected in triplicate from nine sampling sites distributed evenly across teaching, recreational, and residential areas on campus. The soil samples were sieved with a 5 mm screen, and the fractions passing through the sieve were digested with 30% hydrogen peroxide. Microplastics were density-separated from the digested soil and observed under the microscope. ATR-FTIR was used to determine their compositions. This study reveals a higher abundance of microplastics in teaching and residential areas (150–700 items/kg and 50–650 items/kg, respectively) as compared to recreational areas (0–450 items/kg), with the highest mean abundance (516.7 items/kg) recorded for residential areas. Fibrous and fragment microplastics (31.5% and 33.3%, respectively) were most common in the soil samples, with the former more prevalent in residential areas. There were more black microplastics (36.4%) and white microplastics (29.1%) than those of other colors. Microplastics  0.5 mm constituted the largest fraction (64.3%) of total microplastics recovered and polyethylene microplastics were most abundant (35.2%). This study contributes to a better understanding of microplastic pollution in the compounds of higher education institutions, which could be positively linked to the human activities within those institutions.